A love worth giving : living in the overflow of God's love - Lucado, Max. (Nashville, Tenn. : W Pub. Group, 2002)
Pointing out that we must love one another, Lucado issues an impassioned plea to accept God's love in order to truly, unselfishly, whole-heartedly love another.
The 7:47 principle -- Love's flagship -- Your kindness quotient -- Inflamed -- God's "no pecking" zone -- A call to common courtesy -- Getting the "I" out of your eye -- The headwaters of anger -- The heart full of hurts -- The love test -- Love is a package deal -- A cloak of love -- The ring of belief -- When you're low on hope -- He could have given up -- Unfailing love.
Includes bibliographical references (p. 211-214).
Keywords: God (Christianity) -- Love; Love -- Religious aspects -- Christianity; Christian life